2019
DOI: 10.1177/1062860618822752
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Board Certification, Maintenance of Certification, and Surgical Complications in the United States

Abstract: Physician credentialing processes aim to improve patient safety and quality, but little research has examined their direct relationship with surgical outcomes. Using national Medicare claims for 2009 to 2013, the authors studied the association between board certification and completion of Maintenance of Certification (MOC) requirements and surgeon rates of complications for 8 elective procedures. Exemplar surgeons were defined as those in the lowest decile of complication rates, and outlier surgeons were thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Of the 55 studies, three were randomized controlled trials, 37 , 80 , 93 and 52 were observational cohort studies. The studies included various surgical specialties or aggregates thereof, including 8 or more specialties, 81 , 91 breast surgery, 59 , 73 , 74 , 101 cardiac surgery, 44 , 45 , 52 , 53 , 56 , 65–67 , 70 , 89 , 90 , 99 , 100 colorectal surgery, 34 , 61 , 68 , 71 , 78 , 85 , 92 , 103 , 104 ENT surgery, 75 gastrointestinal surgery, 34 , 83 general surgery, 34 , 37 , 57 , 77 , 79 , 82 , 86 , 93 , 95 , 96 , 102 obstetrics, 80 ophthalmology, 97 orthopedic surgery, 55 , 76 , 84 , 102 rectal surgery, 72 , 98 spinal surgery, 58 trauma surgery, 87 and urology. 62–64 , 69 , 88 , 94 , 102 38 studies were conducted in the USA, 10 in the UK, two in Austria and Sweden, one each in Canada, France, and Germany.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 55 studies, three were randomized controlled trials, 37 , 80 , 93 and 52 were observational cohort studies. The studies included various surgical specialties or aggregates thereof, including 8 or more specialties, 81 , 91 breast surgery, 59 , 73 , 74 , 101 cardiac surgery, 44 , 45 , 52 , 53 , 56 , 65–67 , 70 , 89 , 90 , 99 , 100 colorectal surgery, 34 , 61 , 68 , 71 , 78 , 85 , 92 , 103 , 104 ENT surgery, 75 gastrointestinal surgery, 34 , 83 general surgery, 34 , 37 , 57 , 77 , 79 , 82 , 86 , 93 , 95 , 96 , 102 obstetrics, 80 ophthalmology, 97 orthopedic surgery, 55 , 76 , 84 , 102 rectal surgery, 72 , 98 spinal surgery, 58 trauma surgery, 87 and urology. 62–64 , 69 , 88 , 94 , 102 38 studies were conducted in the USA, 10 in the UK, two in Austria and Sweden, one each in Canada, France, and Germany.…”
Section: Resultsmentioning
confidence: 99%
“…Another relevant domain identified in our scoping review was “skills certification,” on which the literature contains conflicting data. Bamford et al 47 demonstrated that improving the technical and nontechnical skills of medical graduates had a positive impact on patient safety, whereas Xu et al 48 found no association between board certification and postoperative complication rates when they analyzed 1.9 million surgical procedures using national Medicare claims for 2009 to 2013. However, the literature about the contribution of skills certification to patient safety in a healthcare professional setting is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al 48 (2019) Association between board certification, maintenance of certification, and surgical complications in the United States. Board-certified surgeons had a 21% lower likelihood of being an outlier (OR = 0.79 [0.66-0.94]), defined as having a complication rate in the highest decile nationwide, but there was no association between board certification and exemplar status.…”
Section: Skills Certificationmentioning
confidence: 99%
“…We believe that the potential effects of policies that increase time cost in an era of physician shortage and aging workforce could be harmful to the general public. Multiple studies have shown an association between MOC participation and fewer negative outcomes 1,[6][7][8][9] . We believe that an evidence-based standard of care is something that should be held in high regard.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of Certification (MOC) remains a controversial topic in medicine today for many reasons, including efficacy, evidence to support the utilization of such of program, and the time required to complete MOC requirements [1][2][3][4][5] . Some research has suggested an association between fewer bad outcomes (loss of license, disciplinary action, surgical complications, etc.)…”
mentioning
confidence: 99%